'Making the Invisible Visible': an audience response to an art installation representing the complexity of congenital heart disease and heart transplantation. Issue 4 (18th October 2018) - Biglino, Giovanni; Layton, Sofie; Lee, Matthew; Sophocleous, Froso; Hall, Susannah; Wray, Jo
Abstract : The arts can aid the exploration of individual and collective illness narratives, with empowering effects on both patients and caregivers. The artist, partly acting as conduit, can translate and re-present illness experiences into artwork. But how are these translated experiences received by the viewer—and specifically, how does an audience respond to an art installation themed around paediatric heart transplantation and congenital heart disease? The installation, created by British artist Sofie Layton and titled Making the Invisible Visible, was presented at an arts-and-health event. The piece comprised three-dimensional printed medical models of hearts with different congenital defects displayed under bell jars on a stainless steel table reminiscent of the surgical theatre, surrounded by hospital screens. The installation included a soundscape, where the voice of a mother recounting the journey of her son going through heart transplantation was interwoven with the voice of the artist reading medical terminology. A two-part survey was administered to capture viewers' expectations and their response to the piece. Participants (n=125) expected to acquire new knowledge around heart disease, get a glimpse of patients' experiences and be surprised by the work, while after viewing the piece they mostly felt empathy, surprise, emotion and, for some, a degree of anxiety. Viewers found the installation more effective in communicating the experience of heart transplantation than in depicting the complexity of cardiovascular anatomy (p<0.001, z=7.56). Finally, analysis of open-ended feedback highlighted the intimacy of the installation and the privilege viewers felt in sharing a story, particularly in relation to the soundscape, where the connection to the narrative in the piece was reportedly strengthened by the use of sound. In conclusion, an immersive installation including accurate medical details and real stories narrated by patients can lead to an empathic response and an appreciation of the value of illness narratives.